Technology‐driven dyadic interaction in caregiving. (31st December 2021) - Hoel, Viktoria; Ambugo, Eliva Atieno; Steinert, Lars; Schultz, Tanja; Wolf‐Ostermann, Karin
Abstract: Background: Due to the ongoing pandemic and the resulting community lockdowns, people with dementia and their family might be at risk of social deprivation and increased relationship strains. Technological means have the potential to engage participants in meaningful positive interactions. The tablet‐based activation system I‐CARE offers social activities specifically designed for people with dementia and their caregivers, by offering user‐specific contents adapted to their needs and sensitivities. Little is known about the impact of Covid‐19 on social health for this population. The ongoing study, presented as a part of the Marie‐Curie Innovative‐Training‐Network action, H2020‐MSCA‐ITN, grant agreement 813196, assesses how COVID‐19 has impacted community‐dwelling dementia caregiving dyads. Contextual factors of technology use and motivations for inviting technology into social interactions is explored. Method: As a part an ongoing pre‐post mixed‐methods feasibility study, baseline assessments through semi‐structured interviews were conducted and subjected to inductive thematic statement analysis by two independent researchers. Result: Participants differed in how COVID‐19 restrictions impacted their lives and how they coped with dementia, revealing different motivations for inviting technology into their lives. Dyads who were socially active pre‐COVID‐19, and who managed use technology to maintain social participation during COVID‐19, reported to have been less negatively impacted by COVID‐19 restrictions. Four subthemes within "Social technology during COVID‐19" were identified. Conclusion: During and beyond this pandemic, social technology is a valuable tool to promote social participation in this population. Successful uptake of technology is dependent on customizing to individuals' needs and conditions.